(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Karshya (undernutrition) is an Apatarpanjanya and Rasa-pradoshaja vyadhi. It is the most large spreading health and nutritional disorder in developing countries. Karshya means person having lean and thin body character without having any more complaints. Karshya is the disease comparable with undernutrition which can be Swatantra Vyadhi (independent disease) a normal phenomenon or it can also manifest along with other diseases as a prestige symptom of complication. It is an Apatarpana Janya Vyadhi (disease caused due to under nourishment) where Vata Dosha plays a very important role in the pathogenesis along with that vitiated Pitta. Vitiated Pachaka Pitta (sub type of Pitta- digestive enzymes) leads to Agni Dushti (impaired digestion) as a result of which the Dhatus are not nourished properly leading to Anuloma Karshaya (depletion of body tissues). Acharya Charaka has well explained clinical symptoms of Karshya. He has explained causative factors in detail which are Aharaja (dietary), Viharaja (behavioural), and Manasika (psychological). “Rasayana therapy” is one of the eight clinical specialties of classical Ayurveda. The nutritional and nourishment deriving function of particular drugs or therapy are known as ‘Rasayana’ in Ayurveda. Ashwagandha (Withania somnifera, fam. Solanaceae) is commonly known as ‘Indian Ginseng’. ‘Ashwagandha Rasayana’ is described as a herbal preparation that promotes a youthful state of physical and mental health. It is known as “Sattvic Kapha Rasayana” Herb (Changhadi, 1938). The various measures of Karshya and Rasayan chikitsa described in the dispersed manner in Ayurveda are collected, compiled and discussed in this research paper.